2011
DOI: 10.1186/1471-2334-11-144
|View full text |Cite
|
Sign up to set email alerts
|

To use or not to use a condom: A prospective cohort study comparing contraceptive practices among HIV-infected and HIV-negative youth in Uganda

Abstract: BackgroundUnwanted pregnancy and HIV infection are issues of significant concern to young people. Limited data exists on contraceptive decision-making and practices among HIV-infected and HIV-negative young people in low resource settings with generalized HIV epidemics.MethodsFrom July 2007 until April 2009, we recruited, and followed up over a one year period, a cohort of 501 HIV-negative and 276 HIV-infected young women and men aged 15-24 years residing in Kampala and Wakiso districts. We compared contracept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 30 publications
6
55
3
Order By: Relevance
“…This finding is lower than findings from similar studies in Swaziland, 60% [24]; Uganda, 59% [9] and 72% [30]; and Canada, 69% [4]; while it is higher than the figures derived from studies conducted in Tanzania, 36% [14]; Uganda, 10% [12], 19% [31], and 29% [11] and Malawi, 17% [5]. In Ethiopia, various studies have reported different level of fertility desire.…”
Section: Discussioncontrasting
confidence: 69%
“…This finding is lower than findings from similar studies in Swaziland, 60% [24]; Uganda, 59% [9] and 72% [30]; and Canada, 69% [4]; while it is higher than the figures derived from studies conducted in Tanzania, 36% [14]; Uganda, 10% [12], 19% [31], and 29% [11] and Malawi, 17% [5]. In Ethiopia, various studies have reported different level of fertility desire.…”
Section: Discussioncontrasting
confidence: 69%
“…Their median age was 39 years (range 27-55), 95% were married, 50% had secondary school or higher education, and 90% were currently on ART. They had a median of four living children (range [1][2][3][4][5][6][7][8], and 95% of the men indicated they or their partner were using a contraceptive method, with 28% indicating dual method use, using condoms along with a more effective contraceptive method (see Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…3 The need and desire for FP services is substantial among HIV-positive persons in both resource-limited [4][5][6][7][8][9][10] and resource-rich [11][12][13][14] settings. The unmet need for FP services is particularly high in Kenya; one study found that nearly 70% of HIV-positive women in western Kenya indicate wishing to delay their fertility for another 2 years or not have any further children.…”
mentioning
confidence: 99%
“…Exceptions to this trend include two studies that showed lower contraceptive use among HIV-infected youth and HIV-infected female sex workers compared to their HIV-uninfected counterparts. [20, 33] Factors associated with contraceptive use by people living with HIV are similar to those identified for the general population, and are primarily not related to HIV status [14, 24, 27, 30, 31, 34]. However, one study reported that fear of ART interactions was a reason for not using contraception and another indicated that beliefs about a lower survival rate for HIV-infected children was a reason for use [14, 26].…”
Section: Fertility Intentions Family Planning Use Unintended Pregnamentioning
confidence: 93%
“…Those who do not wish to become pregnant can be supported to access and use contraception. Though fertility desire may increase for some women after starting ART, recent data suggest that on average HIV-infected women tend to want fewer children than HIV-uninfected women [19, 20, 21*]. In one study, HIV status was the firmest predictor of not wanting future children [21].…”
Section: Fertility Intentions Family Planning Use Unintended Pregnamentioning
confidence: 99%